Hidden Cost Marketing: Descriptive Analysis of Digital Marketing Strategies and Creating Branding for MSMEs - Sugiana, Neng Susi Susilawati; Rahayu, Agus; Wibowo, Lili Adi; Gafar, Vanessa; Dirgantari, Puspo Dewi (Politeknik Negeri Bandung, 2023)
This research aims to see how MSME businesses can ultimately apply digitization in their marketing activities so that it is expected to strengthen the branding of a product. It is also intended to see the implications that occur for hidden costs or costs that often arise and are unexpected when marketing their products. This study uses a quantitative analysis methodology with a population of 520 SMEs in Bandung with various business categories and who already have business licenses. Data were collected using questionnaires and interviews with MSMEs from field analysis and it shows that MSMEs are still the driving force of the economy in the city of Bandung, despite experiencing obstacles during the 2020-2021 outbreak. Good opportunities can be captured to implement digital marketing, as evidenced by the emergence of brand-new local brands that are much sought-after or increasingly recognized products from MSMEs with a wider range. The results of the analysis state that in the last two years, MSME players have maximized the implementation of digital marketing to produce a strong brand and reduce costs that often occur when marketing is carried out directly, especially hidden costs that are not included in business accounting calculations. So, marketing carried out by implementing digital marketing is effective in building a strong brand and reducing hidden marketing costs.